Pengembangan Media Flipbook Berbasis Augmented Reality pada Muatan Pelajaran Ilmu Pengetahuan Alam Materi Ekosistem - Kurnia Lita Cahya; Kurniana Bektiningsih (Postgraduate, University of Mataram, 2024)
This research aims to develop flipbook media based on augmented reality using ecosystem material. Research and Development (R&D) is the research method used, while ADDIE is a development model consisting of analysis, design, development, implementation, and evaluation. Tests and non-tests are used for data collecting, while qualitative and quantitative methods are employed for data processing. The study's participants comprised 22 fifth-grade pupils and an educator from SDN Sidomulyo 3. The outcomes demonstrated how extremely possible it is to use Flipbook media with augmented reality for education. Media, material, and language expert validation scored 90, 94, and 92%. The normality test results indicate that the data is normally distributed, with the Sig. The pretest value was 0.74 > 0.05, and the Sig. Postest value of 0.14 > 0.05. A paired sample t-test showing the impact of employing Augmented Reality-based Flipbook media in learning, with a Sig. (2-tailed) 0.00 < 0.05. The n-gain test shows 0.78 with a high category. In light of these findings, it may be said that augmented reality-based Flipbook media is feasible and effective for learning IPAS Ecosystem content in grade V elementary school.